Avaliação de dois métodos de extração de DNA em amostras obtidas por swab associados às técnicas moleculares de PCR convencional, PCR em tempo real e LAMP para o diagnóstico da leishmaniose tegumentar - Verônica Cardoso Santos de Faria (2020)
Background: Tegumentary leishmaniasis (TL) has a limited diagnostic arsenal and involves the use of invasively collected specimens. The Leishmania DNA search on swab-collected material may be a minimally invasive and accurate strategy for the molecular diagnosis of TL. The accuracy of molecular assays can be affected depending on the type of sample and the DNA extraction method used. The extracted DNA quality and yield parameters are critical points for detection and identification of Leishmania species by nucleic acid amplification. Objective: To compare two DNA extraction methods (PureLink™ Genetic DNA Mini-Kit and Direct Boil - DB technique) in swab samples from patients with CL and ML, and the use of these samples for molecular detection and genotyping of Leishmania. Methods: Twenty-six patients with TL (13 CL and 13 ML) coming from outpatient clinics of the Instituto René Rachou /FIOCRUZ and the Hospital das Clínicas/UFMG were evaluated. All cases had their diagnosis confirmed by kDNA cPCR in biopsy samples. DNA yield and quality in swab samples were measured by spectroscopy and DNA integrity was assessed by polyacrylamide gel electrophoresis. The extracted DNA was tested by four molecular diagnostic tests (kDNA cPCR, SSU TaqMAN qPCR; kDNA SYBR-qPCR; and rRNA LAMP-RT 18S) and a molecular test for genotyping (hsp70 PCR-RFLP). For indirect quantification of parasitic load, an analysis of threshold cycle (CT) values was performed by SYBR qPCR kDNA. Results: The DB protocol resulted in the highest DNA yield (196 ng/µL - ML; 95.6 ng /µL - CL) as compared to the commercial kit. The commercial kit protocol gave the highest genetic quality using an A260/A280 ratio for DNA purity (ML: 1.81 ng / µL; and CL: 1.93 ng/µL). Both extraction methods presented non-standard absorbance values recommended in the A260/A230 ratio analysis, and DB technique had the worst result (ML: 0.42; CL: 0.3). The DNA integrity was affected in 92.3% of swab samples (CL and ML) extracted by DB technique. The DNA integrity was maintained in most samples obtained by swab and extracted by the Purelink ™ kit, with identical or higher performance in all molecular techniques performed in comparison with tests with samples obtained by biopsy. Only in kDNA cPCR with samples from CL cases, the performance of samples collected by swab and extracted by the DB technique was identical when compared to swab extraction using the commercial kit. TaqMan SSU rRNA qPCR performed using swab together with DB extraction showed the worse sensitivity results for CL (46%) and ML (23%). Leishmania braziliensis was the only specie found in all analyzed samples, and the genotypic characterization have a best performance in samples collected by swab and extracted by the commercial kit for CL and in biopsy samples for ML. Conclusion: The use of swab as a minimally invasive sampling method can be a low-cost alternative for the molecular diagnosis of TL, having great applicability to remote regions. For CL, the use of swab coupled with extraction by commercial kit showed high performance regardless of the molecular technique used; while for ML this association showed better sensitivity in cPCR kDNA. The use of the DB technique for swab extraction requires attention, as the sensitivity of the molecular techniques evaluated varied widely. The general precision of the extraction methods and molecular techniques using swab should be analyzed in a larger sample group, which may confirm the applicability of this non-invasive strategy for the diagnosis and characterization of the species causing the disease.